The Influence of Social Media Marketing, Electronic Word of Mouth and Consumer Engagement to Brand Loyalty: Study Case at the DOTA 2 - Moses Lorensius Parlinggoman Hutabarat; Christopher Leonard (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
Online gaming is a new phenomenon in the era of internet information technology. Indonesia has a very big opportunity in the gaming industry. But unfortunately, Indonesian game developers have difficulty competing in the local market. This research will be conducted on the analysis of the gaming industry, particularly on the multiplayer online battle arena (MOBA) category of games. The problem in this study is the gap between the online gaming industry and the decline of DOTA2. This study examined 120 respondents of the online games customers using online questionaires. This research using the PLS-SEM data analysis method. Based on the results of data processing, it was found that the hypothesis of social media marketing variable has positive influence on the customer engagement was rejected, the electronic word of mouth variable has a positive influence on customer engagement was rejected, the social media marketing variable has positive influence on the brand loyalty variable was rejected, the electronic word of mouth variable has a positive influence on the brand loyalty was rejected, and the customer engagement variable has a positive influence on the brand loyalty.